Food sustainability in times of crises a deductive study from the Holy Qur’ān, chapter 12 (Yūsuf/Joseph) - Alsallom, Ahmad Fares (Edelweiss Applied Science and Technology, 2024)
This article explores the concept of food sustainability in times of crisis, drawing insights from the Qur’ānic narrative of Joseph. It delves into Joseph’s comprehensive plan, outlining its key principles, implementation strategies, and the positive outcomes it achieved for Egypt and neighbouring regions. The research seeks to present Joseph’s plan as a model for addressing food crises, his plan for food sustainability during the seven years crisis that Egypt went through as a result of the famine. It examines the foundational principles that guided his strategy, the steps taken to implement it, and the ultimate results. The research concludes with several key findings: Food sustainability in times of crises requires a carefully designed policy centred on strategic stockpiling. On the other hand, successful implementation hinges on a deep understanding of the plan’s components and a steadfast commitment to its execution.